Pengaruh Kurs Dollar Amerika, Jumlah Produksi Dan Luas Lahan Pada Volume Ekspor Lada Indonesia - Umantari, Ni Wayan Jesni; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 5, Mei 2015 (pp. 348 - 607), 2015)
Oil as one of  raw material in production process of goods and service is vital factor in support production activity in Indonesia. Indonesia previous is a state as producer of oil and one of member of organization of petroleum exporting country (OPEC) but its reality still not yet able to fulfil the domestic’s need. This study aims to find out the effect of per capita income, price, US dollar rate and reserve of devisa simultaneously and partially toward oil import in Indonesia. Object in this study were per capita income, price, US dollar rate, reserve of devisa and oil import. Type of data has been applied in this study was secondary data. Data analysis technique was applied multiple linear regression.  The result showed simultaneously the variable of per capita income, price, US dollar rate, and reserve of devisa have significant effect toward import of oil in Indonesia. Partially percapita income and reserve of devisa have positive and significant toward import of oil Indonesia. Partially price and US dollar rate have negative significant toward import of oil in Indonesia. The government should decrease import of oil so that price will reduce and rupiah rate will  increase hence reserve of devise will improve. By existence reduction of import hence oil subsidy will decrease so that subsidy can be switch for purpose to improve education and health.
Keywords: Pendapatan Perkapita; Harga; Kurs Dollar Amerika Serikat; Cadangan Devisa; Impor Minyak Bumi